ANALISIS TINGKAT KESEGARAN JASMANI SISWA SMA PUTERA KELAS X (STUDY PADA SMA PGRI 1, SMA NEGERI 2 DAN 3 JOMBANG) - PERMANA P, ALAMSYAH Permana (Jurnal Prestasi Olahraga, 2013)
Physical fitness is the ability of one's body to perform daily work tasks without causing significant fatigue, so that the body still has the energy reserves to cope with the extra workload. Problems can be formulated as follows: how the Analysis of Physical Fitness High School Students of Class X Men (Study on SMA PGRI 1, State SMA 2 and SMA 3 Jombang)?The purpose of this research was to determine the level of physical fitness Son High School Students of Class X (PGRI SMA 1, SMA 2 and 3 Jombang) by Fitness Test Physical (TKJI) and to find out which is better physical fitness level high school students Son Class X Men ( PGRI SMA 1, State SMA 2 and 3 Jombang) Physical fitness test by Indonesia (TKJI).The method of data collection using descriptive methods test and measurement techniques, while the instrument used is fitness Physical Test (TKJI). For the 16-19 year age category which consists of 5 items that test: run 60 yards, lifting body (pull ups), recline seat (shit up), jump upright (vertical jump) and the 1200 meter run.Based on the research that has been conducted on physical fitness tests at the High School Students of Class X Men (SMA PGRI 1, State SMA 2 and 3 Jombang) consisting of 5 test items, it can be concluded that: the average value of physical fitness in the school SMA PGRI 1 Jombang (9.7%) both categories, (54.8%) category, (35.5%) less category, at State SMA 2 Jombang (59.1%) category, (40.9%) less category , whereas in State SMA 3 Jombang (3.8%) categories very well, (11.5%) good category (65.4%) category (19.2%) less category. The authors wish to penjaskes teachers in each school could provide more varied materials and inofatif penjaskes with the element of fun and the students should be able to improve physical fitness by continuing to perform physical activities after hours penjaskes.Keywords: Level High School Physical Fitness